2016
DOI: 10.1002/cjce.22521
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of microwave heating method in production of activated carbon

Abstract: This work investigates the chemical activation of a biochar sample using microwaves with KOH and NaOH. The activation of char samples was carried out in a microwave oven operating at 2.45 GHz with a power input of 1200 W. The specific surface area (SSA), yield (%), and pore size distribution were studied for microwave activation with KOH and NaOH. In microwave‐assisted activation, the activation yields for NaOH and KOH activation were in the ranges of 40–70 % and 60–80 %, respectively. The NaOH‐activation take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…8,10 Recent studies employing microwave energy as the mode of heating in carbonization step of AC production from biomass proved that heating time is significantly reduced compared to that in conventional furnaces. Namazi et al (2016) produced chemically activated carbon out of biochar from pulp mill sludge with similar surface area in 2 h under 600 °C conventional heating and in 5 min under 1200 W microwave. 12 A similar study produced comparable textural properties of activated carbon from sewage sludge heated in a 500 °C furnace in 15 min and in a 980 W microwave in 12 min.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,10 Recent studies employing microwave energy as the mode of heating in carbonization step of AC production from biomass proved that heating time is significantly reduced compared to that in conventional furnaces. Namazi et al (2016) produced chemically activated carbon out of biochar from pulp mill sludge with similar surface area in 2 h under 600 °C conventional heating and in 5 min under 1200 W microwave. 12 A similar study produced comparable textural properties of activated carbon from sewage sludge heated in a 500 °C furnace in 15 min and in a 980 W microwave in 12 min.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Namazi et al (2016) produced chemically activated carbon out of biochar from pulp mill sludge with similar surface area in 2 h under 600 °C conventional heating and in 5 min under 1200 W microwave. 12 A similar study produced comparable textural properties of activated carbon from sewage sludge heated in a 500 °C furnace in 15 min and in a 980 W microwave in 12 min. 13 Activated carbon derived from raw bamboo chemically activated by H 3 PO 4 was observed to have a faster activation rate and higher yield under microwave heating.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[ 64 ] Therefore, employing alternative energy sources such as microwave irradiation can reduce the energy usage and other negative environmental impacts of synthesis processes, which is of high importance. In literature, there are many papers devoted to pyrolysis, [ 65–74 ] activation, [ 75–98 ] and even regeneration of spent carbons [ 99–106 ] under microwave radiation. Recently, excellent reviews were reported to summarize the main accomplishments in the microwave‐assisted synthesis of biomass‐derived porous carbons.…”
Section: Microwave Synthesis Of Nanoporous Materials and Their Applicationsmentioning
confidence: 99%
“…Porous carbons obtained via microwave‐assisted methods with their SSA values and potential applications are summarized in Table 4 . [ 65–122 ]…”
Section: Microwave Synthesis Of Nanoporous Materials and Their Applicationsmentioning
confidence: 99%
“…However, because of the selective heating of the microwave, many precursors cannot be carbonized by microwave heating. Similarly, in the study of Namazi et al 6 and Duan et al, 7 sludge and cotton were adopted to make activated carbon, and the samples were activated with the assistance of microwaves. At present, the so-called "microwave-assisted" actually refers to the use of microwaves during the activation part.…”
Section: Introductionmentioning
confidence: 99%